The Role of Principal in Improving Competitive Advantage of Early Childhood Education Institution - Wahyuni, Sri; Supriyono, Supriyono (Journal of Nonformal Education, 2018)
This study aims to identify and explain the role of principal in improving the competitive advantage of Early Childhood EducationÂ  institution. The research approach used is qualitative research with multicase study design. The study was conducted at two ECE institution in Malang, namely Restu 2 and As Salam. Data collection was done by in-depth interview, observation, and documentation study, then analyzed by inductive analysis method, which includes two stages: individual site data analysis and cross-site data analysis. Key research informant is principal. Data validity checking is done through credibility test, transferability test, and confirmability test. The results of this study indicate that the role of principal in improving the competitive advantage of ECE institution is categorized in 3 roles, namely (1) as a drafter that plays a role in developing creative ideas and drafting innovative program concepts to make the institution known to the public; (2) as a liaison, which plays a role in conveying the vision of the mission to the members of the institution and establish cooperation with other parties or parents; and (3) as a controller, that is to play a role in maintaining the quality of service institutions through the activities of dividing educator tasks according to their respective expertise, building a family atmosphere, and monitoring the implementation of educator's duties.